THE EMERGENCE OF A KNOWLEDGE AGGLOMERATION: A SPATIO-TEMPORAL ANALYSIS OF INTELLECTUAL CAPITAL IN INDIANA - Brigitte Waldorf (European Regional Science Association (ERSA), 2005)
U.S. States and communities increasingly compete for intellectual power so as to thrive toward an economically vibrant setting that spurs the entrepreneurial spirit and attracts businesses and industries from around the world. As a recent report by the U.S. census reveals, 17 U.S. States have gained such intellectual power through the net inmigration of young, single and college educated persons. The State of Indiana is among the remaining thirty-three States that have a negative net balance, even ranking among the bottom ten in their ability to attract this highly valued population segment. In fact, for every young, single, college educated inmigrant, Indiana loses nearly two to other states. However, an analysis at the state-level hides important small-scale variations. This paper therefore investigates the processes leading to changes in the spatial distribution of knowledge workers across Indiana counties, with emphases on in-situ change, retention, intra- and interstate migration. The analysis shows that these demographic changes at the county level in fact reveal a less bleak picture than the state-wide aggregate figures suggest, and uncover remarkable peaks in the landscape of intellectual capital that can serve as a catalyst for attracting intellectual capital from outside the State.
Keywords: 330